If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
2*x-((5/8)*y) = 1/6 // - 1/6
2*x-((5/8)*y)-(1/6) = 0
2*x+(-5/8)*y-1/6 = 0
2*x-5/8*y-1/6 = 0 // + -5/8*y-1/6
2*x = -(-5/8*y-1/6) // : 2
x = (-(-5/8*y-1/6))/2
x = (1/6-(-5/8*y))/2
x = (1/6-(-5/8*y))/2
| 6p+29-34=919 | | 17f+6-7f=2 | | 0=3x^2-6x-297 | | (z^(5/2)*x^(-4))^(1/3) | | 9t^3-144t=0 | | (9a^3+a-3)-(6-3a^3-8a^2)= | | 8y^9-8y^8-96y^7=0 | | (z^(5/2)*x^-4)^(1/3) | | -(8y+2)-(-7y-3)=-6 | | x-y/4 | | x^2=3(2x-3) | | 3x^2-2y-8=0 | | -x-5y=15 | | 6(4x-3)=2(12x+9) | | 6+4t-2=7t+12-2t | | x^2/70 | | 3/2ln(16x^2)-2/5ln(2y^25) | | 9x+3=5-(5x-5) | | (x^2+x-5)= | | 6x-y=-32 | | 5h=t-5u | | -x^4-4x^2-16=0 | | t-5u=5h | | 9y+7y=96 | | -x^4+4x^2+16=0 | | (-9x+1)= | | (-9x+1)+(x^2+x-5)= | | 3-7(8-5x)=0 | | 4-6(7x+2)=9 | | (8/17)/(3/5) | | (5/8)*16 | | 8+6m-3=9m+9-2m |